Part and electrophoretic coating process and application thereof

By using zirconization treatment liquid containing hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite, the problem of long zirconization treatment time and the need for rust prevention after zirconization is solved, and the electrophoretic coating efficiency is improved and the good corrosion resistance of the parts is achieved.

CN120006364APending Publication Date: 2025-05-16DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411270593.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-05-16

AI Technical Summary

Technical Problem

The existing zirconization treatment process has a long time for zirconization, and the washing process after zirconization requires the addition of anti-dry spray or anti-rust agent to prevent parts from rusting, and the electrophoretic coating efficiency is low.

Method used

A zirconization treatment liquid is provided, including hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite. The components are zirconized by the liquid to shorten the treatment time, and immersing them in the zirconization treatment liquid for 120s to 140s can obtain a qualified zirconization film, and the anti-rust treatment is omitted.

Benefits of technology

The zirconization treatment time is shortened, the anti-rust treatment after zirconization is avoided, the efficiency of the electrophoretic coating process is improved, and the components are kept rust-free during the 1000-hour salt spray test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120006364A_ABST
    Figure CN120006364A_ABST
Patent Text Reader

Abstract

The invention relates to a part and an electrophoretic coating process and application thereof, and belongs to the technical field of electrophoretic coating. The zirconium treatment liquid provided by the invention comprises hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride and sodium nitrite; wherein aluminum nitrate can reduce the concentration of free fluorine in the treating fluid and promote hydrolysis of hexafluorozirconic acid, so that the generation speed of a zirconium film is increased; and the sodium nitrite can prevent the part base material from rusting, so that the anti-rust treatment after zirconium treatment is omitted. A part only needs to be subjected to zirconium treatment in the zirconium treatment liquid for 120 s, a zirconium film with the film weight being 48 mg / m < 2 > can be obtained, anti-dry spraying or anti-rust agent spraying does not need to be carried out after zirconium treatment to prevent the part from being rusted, and compared with the prior art, the efficiency of the electrophoretic coating process is improved; the parts subjected to electrophoretic coating are still free of corrosion after being subjected to a salt spray test for 1000 hours, and compared with the prior art, the performance is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrophoretic coating, and relates to a component and an electrophoretic coating process and application thereof. Background Art

[0002] The frame is generally made of cold-rolled steel plates, which are connected together through stamping and welding processes, and then some cast aluminum parts are assembled to form a complete frame structure, and then integrated phosphating and painting are carried out. The frame is the matrix of the car, and the use environment requires it to have good corrosion resistance. At present, the most widely used process for the frame is the electrophoretic coating process that matches the phosphating pretreatment with cathode electrophoresis. Its process flow is: pre-degreasing → main degreasing → water washing 1 → surface adjustment → phosphating pretreatment → water washing 2 → pure water washing 1 → pure water washing 2 → cathode electrophoresis → electrophoretic ultrafiltrate 1 (UF1) → electrophoretic ultrafiltrate 2 (UF2) → pure water washing 3 → pure water washing 4. The above electrophoretic coating process has the following problems: because the phosphating tank contains heavy metal ions, wastewater containing toxic heavy metals such as zinc, manganese, and nickel is produced after phosphating, which is poor in environmental protection; when multiple plates (cold-rolled steel plates, aluminum profiles, galvanized plates, etc.) are phosphated on the same line, the amount of sediment is large.

[0003] Zirconization technology is a new technology that uses zirconization liquid to treat the surface of the substrate. The nano-scale conversion film formed on the surface of the substrate is amorphous ZrO2, rather than polycrystalline Zn3(PO3)2. This technology is considered to be an alternative technology that can replace phosphating technology. However, the existing technology believes that: the surface morphology of the substrate has a greater impact on the zirconization film. If the microscopic state of the substrate surface is inconsistent, the state and film weight of the zirconization film after the reaction will be different, which will directly affect the difference in the state of the electrophoretic film. In addition, the parameter control range of the zirconization film is much smaller than that of the traditional phosphating process, and the stability is poor; the temperature also has a significant impact on the zirconization effect, and the bath liquid parameters need to be adaptively adjusted according to the air temperature.

[0004] A Chinese patent document with publication number CN108998781A and publication date December 14, 2018 discloses a zirconization treatment process for the front surface of a car body before painting, which includes the steps of washing the workpiece with hot water, pre-degreasing, main degreasing, washing before zirconization, zirconization treatment and washing after zirconization in sequence, and the temperature of hot water washing, pre-degreasing and main degreasing is 45-55°C, and the pH value of the zirconization liquid is controlled to be 4-5, the F content is 20-70ppm, the treatment time is 150-180s, and the temperature is 25-45°C. The zirconization treatment process has a long zirconization treatment time, and the cold-rolled plate will rust after 6 minutes in the air after zirconization treatment. The washing process after zirconization needs to prevent the body from rusting by adding anti-dry spray or rust inhibitor. Summary of the invention

[0005] The present invention provides a component and an electrophoretic coating process and application thereof, so as to solve the problems that the existing zirconization process has a long zirconization treatment time and the washing process after zirconization needs to add an anti-drying spray or a rust preventer to prevent the component from rusting.

[0006] In order to achieve the above object of the invention, the first aspect of the present invention provides a zirconization treatment solution, which comprises hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite.

[0007] In some embodiments of the present invention, the Zr element concentration in the zirconization treatment solution is 2-5 pt, the pH value is 3.8-4.5, the free fluoride ion concentration is 20-50 mg / L, the aluminum nitrate concentration is 50-100 ppm, and the sodium nitrite concentration is 50-100 ppm.

[0008] A second aspect of the present invention provides an electrophoretic coating process, wherein the process flow of the electrophoretic coating process is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing;

[0009] The zirconization pre-treatment comprises:

[0010] Immerse the parts in the zirconization treatment solution at 20 to 40°C for 120 to 140 seconds, remove them, and proceed to the next step.

[0011] In some embodiments of the present invention, the cathode electrophoresis comprises: immersing the component in a cathode electrophoresis solution at 28 to 32° C. for 180 to 220 seconds.

[0012] In some embodiments of the present invention, the components include steel components and aluminum components.

[0013] In some embodiments of the present invention, in the cathode electrophoresis solution:

[0014] The solid content is 19 wt% to 25 wt%; and / or,

[0015] The ash content is 15wt% to 21wt%; and / or,

[0016] pH value is 5.6 to 6.7; and / or,

[0017] The electrical conductivity is 1200 to 2000 μs / cm; and / or,

[0018] One voltage is 190~210V; and / or,

[0019] The second stage voltage is 285~315V.

[0020] In some embodiments of the present invention, the conductivity of the water in the second pure water washing and the third pure water washing is controlled to be ≤500μs / cm; and / or, the free alkali of the degreasing agent used in the pre-degreasing and main degreasing is 9.0-12.0, and the treatment temperature is 42-50°C.

[0021] A third aspect of the present invention provides a component, which is processed by the above-mentioned electrophoretic coating process.

[0022] In some embodiments of the present invention, the component is a steel-aluminum hybrid frame or a steel-aluminum hybrid body.

[0023] A fourth aspect of the present invention provides a vehicle comprising the above-mentioned components.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] 1. The parts only need to be zirconized in the zirconization solution of the present invention for 120 seconds to obtain 48mg / m 2 The zirconized film is formed, and there is no need to carry out anti-drying spraying or anti-rust agent spraying after zirconization to prevent parts from rusting, which improves the efficiency of the electrophoretic coating process compared with the existing technology.

[0026] 2. The parts after electrophoretic coating of the present invention are still free of rust after 1000 hours of salt spray test, which is a significant improvement over the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 : Photograph of the zirconized cold-rolled steel sheet of Example 1 after undergoing a 1000-hour salt spray test.

[0029] Figure 2 : Photograph of the zirconized cold-rolled steel sheet of Comparative Example 1 after undergoing a 1000-hour salt spray test.

[0030] Figure 3 : Photograph of the zirconized cold-rolled steel sheet of Comparative Example 2 after undergoing a 1000-hour salt spray test. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0033] It should be noted that, in the description of this article, unless otherwise specified, "above", "below" include the number, and the meaning of "multiple" in "one or more" is two or more. Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.

[0034] In the description of this specification, the description with reference to the terms "any embodiment / method", "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0035] The term "pt" of the present invention means nanograms per liter.

[0036] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. These embodiments can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0037] Zirconium treatment liquid

[0038] As described in the background technology, phosphating pre-treatment will produce wastewater containing toxic heavy metals such as zinc, manganese, and nickel, which is environmentally friendly, and the amount of sediment is large when multiple plates (cold-rolled steel plates, aluminum profiles, galvanized plates, etc.) are produced on the same line. Compared with the electrophoresis process using phosphating pre-treatment, the zirconization process does not contain toxic heavy metals such as zinc, manganese, and nickel in the wastewater, and the amount of waste residue is small. The existing zirconization process takes a long time for the zirconization of parts, and the washing process after zirconization needs to prevent the body from rusting by adding anti-dry spray or rust inhibitor, and the efficiency of electrophoretic coating is low.

[0039] The existing zirconization treatment solution is mainly composed of hexafluorozirconic acid (H2ZrF6). The metal substrate undergoes an electrochemical reaction in the zirconium salt acid solution to form a nano-scale zirconium film, which provides excellent corrosion resistance for the metal substrate surface. The zirconium salt film formation process is as follows:

[0040] Metals react with acids:

[0041] Me+2H + →Me 2+ +H2

[0042] Zirconate dissociation:

[0043] H2ZrF6→ZrF6 2- +2H +

[0044] Zirconate precipitation:

[0045] Me 2+ +ZrF6 2- +H2O→MeZrF6·2H2O

[0046] Based on this principle, the inventors added nitric acid and hydrogen fluoride to promote the conversion of metal element Me to metal ion Me 2+ The conversion of ZrF6 was inhibited by adding aluminum nitrate 2- To free fluorine F - In addition, hydrogen fluoride also inhibits ZrF6 2- To free fluorine F - The effect of conversion is to promote the generation of MeZrF6·2H2O and increase the rate of zirconization. Based on this, the present invention provides a zirconization treatment liquid, which contains hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite. Using the zirconization treatment liquid to treat parts can shorten the zirconization treatment time and omit the anti-corrosion measures after the zirconization treatment.

[0047] In some embodiments of the present invention, the Zr element concentration in the zirconization treatment solution is 2-5 pt, the pH value is 3.8-4.5, the free fluoride ion concentration is 20-50 mg / L, the aluminum nitrate concentration is 50-100 ppm, and the sodium nitrite concentration is 50-100 ppm.

[0048] The weight of zirconium film is generally 30~70mg / m 2 If the zirconium film is too thick, it will have an adverse effect on the subsequent electrophoresis process. In the zirconium treatment solution, the Zr element concentration is 2-5 pt, and the free fluorine ion concentration is 20-50 mg / L, which can ensure that the zirconium film weight is within the above range, and the zirconium film unilateral corrosion expansion is ≤2 mm, with good anti-corrosion ability; and does not affect the adhesion of the zirconium film to the electrophoretic paint film.

[0049] The pH value of the zirconization treatment solution is 3.8 to 4.5, which can ensure that the metal element Me is converted to metal ions Me 2+ The conversion rate will not inhibit the dissociation rate of H2ZrF6.

[0050] The concentration of sodium nitrite in the zirconization treatment liquid is 50-100 ppm, which can ensure that the parts have good anti-rust ability without anti-rust treatment.

[0051] Electrophoretic coating process

[0052] The present invention provides an electrophoretic coating process, wherein the process flow of the electrophoretic coating process is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing;

[0053] The zirconization pretreatment includes: immersing the parts in a zirconization treatment solution at 20 to 40° C. for 120 to 140 seconds, removing them, and proceeding to the next step; the zirconization treatment solution used in the electrophoretic coating process contains hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite.

[0054] In the electrophoretic coating process, aluminum nitrate is added to the zirconization treatment liquid, and the aluminum nitrate is hydrolyzed to produce aluminum hydroxide. The aluminum hydroxide reacts with free fluorine in the zirconization treatment liquid to form a solid precipitate, thereby reducing the free fluorine concentration in the zirconization treatment liquid and promoting the hydrolysis of hexafluorozirconic acid, thereby shortening the zirconization treatment time. The present invention also adds sodium nitrite to the zirconization treatment liquid to prevent parts from rusting, thereby avoiding the need to add anti-drying spray or rust inhibitor in the subsequent water washing process to prevent parts from rusting.

[0055] The zirconization pre-treatment of the present invention only requires the parts to be immersed in the zirconization treatment liquid for 120s to 140s to obtain a qualified zirconization film weight. Compared with the prior art that requires the parts to be immersed in the zirconization treatment liquid for more than 150s, the immersion time of the parts in the zirconization treatment liquid is shortened; the present invention does not need to add anti-drying spray or rust inhibitor after the zirconization pre-treatment, simplifies the process steps, and further shortens the process flow of the electrophoretic coating process.

[0056] Furthermore, the zirconization treatment liquid used in the electrophoretic coating process has a Zr element concentration of 2 to 5 pt, a pH value of 3.8 to 4.5, a free fluoride ion concentration of 20 to 50 mg / L, an aluminum nitrate concentration of 50 to 100 ppm, and a sodium nitrite concentration of 50 to 100 ppm.

[0057] Without intending to limit the process parameters of cathode electrophoresis, in some embodiments of the present invention, cathode electrophoresis includes: immersing the parts in cathode electrophoresis solution at 28-32° C. for 180-220 seconds. This condition is mild and has low energy consumption; the parts are immersed in the cathode electrophoresis solution for a short time and the electrophoresis efficiency is high.

[0058] The cathode electrophoresis liquid used in the electrophoresis process of the present invention can be prepared using common aqueous cathode electrophoresis coatings. The main components of common cathode electrophoresis liquids are base resin, cross-linking resin, neutralizer and replenishing solvent. The base resin is generally epoxy polyamide modified or polyester modified resin, the cross-linking resin is generally blocked isocyanate resin, the neutralizer is generally organic acid, and the replenishing solvent is generally alcohol, alcohol ether and ketone solvent. There is no intention to limit the type of cathode electrophoresis liquid. In some embodiments of the present invention, the cathode electrophoresis liquid is prepared from one of HT-8000C (purchased from Kansai Paint, Japan), Nippon Paint 1421, and PPG ED8000. The prepared cathode electrophoretic liquid has a solid content of 19wt% to 25wt%, an ash content of 15wt% to 21wt%, a pH value of 5.6 to 6.7, a replenishing solvent content of 0.2wt% to 1.0wt%, and a conductivity of 1200 to 2000μs / cm, which can ensure that the parts after electrophoretic coating have good anti-corrosion effect. In the embodiment of the present invention, the coated parts are still free of rust after 1000 hours of salt spray test.

[0059] Taking the HT-8000C cathode electrophoretic coating produced by Kansai Paint as an example, the HT-8000C cathode electrophoretic coating includes color paste F-1, emulsion F-2, neutralizer F-3A, and replenishing solvent F-3E. Taking the target preparation of 3500g cathode electrophoretic liquid as an example, the volume ratio of each component is: color paste (F-1): emulsion (F-2): pure water: F-3A = 321: 1717: 1457.4: 4.6, and replenishing solvent (F-3E) is added at 0.2wt% to 1.0wt% of the content of the cathode electrophoretic liquid.

[0060] There is no intention to limit the materials of parts and components. The electrocoating process of the present invention can be used not only for the surface coating of steel parts and components, but also for the surface coating of aluminum parts and components, and can be used for the surface coating of galvanized parts and components. The prior art believes that the microscopic state of the substrate surface is inconsistent, and the state and weight of the zirconized film after the reaction are different, which will directly affect the difference in the state of the electrophoretic film. The surface microstructures of steel, aluminum, and zinc are obviously different. After the steel parts, aluminum parts, and galvanized parts are assembled into one and zirconized, the quality of the zirconized film obtained is prone to differences, resulting in obvious differences in the quality of the electrophoretic film. The electrophoretic coating process of the present invention is suitable for the surface coating of mixed material parts including any one, two combinations, or three combinations of steel parts, aluminum parts, and galvanized parts, such as: cold-rolled steel plate parts, steel-aluminum mixed parts, steel-zinc mixed parts, aluminum-zinc mixed parts, and steel-aluminum-zinc mixed parts.

[0061] There is no intention to limit the type of cathode electrophoresis liquid of the present invention. The cathode electrophoresis liquid used in the present invention is:

[0062] The solid content is 19 wt% to 25 wt%; and / or,

[0063] The ash content is 15wt% to 21wt%; and / or,

[0064] pH value is 5.6 to 6.7; and / or,

[0065] The electrical conductivity is 1200 to 2000 μs / cm; and / or,

[0066] One voltage is 190~210V; and / or,

[0067] The second stage voltage is 285~315V.

[0068] The present invention performs flood flushing on the substrate before zirconization pretreatment, that is, industrial water is used to remove loose pollutants on the surface of the substrate to prevent the pollutants from contaminating the zirconization treatment liquid.

[0069] The present invention performs pre-degreasing and main degreasing on the substrate before zirconization pretreatment. The pre-degreasing adopts a spraying method, and the main degreasing adopts an immersion method, which can clean the organic pollutants on the surface of the substrate and prevent the organic pollutants from hindering the contact between the zirconization treatment liquid and the substrate surface, resulting in an uneven zirconization film on the substrate surface. The free alkali of the degreasing agent used in the pre-degreasing and main degreasing is 9.0-12.0, and the treatment temperature is 42-50°C. The temperature is higher than room temperature to improve the efficiency of removing organic pollutants. The pre-degreasing and main degreasing of the present invention can use common commercially available degreasing agents.

[0070] The present invention sequentially performs a second pure water wash and a third pure water wash after the zirconization pre-treatment, the purpose of which is to wash away the zirconization treatment liquid on the surface of the substrate. The second pure water wash and the third pure water wash of the present invention control the conductivity of water to be ≤500μs / cm. Preferably, the second pure water wash is performed by spraying, and the third pure water wash is performed by immersion, so that the residual zirconization treatment liquid on the surface of the substrate can be removed as completely as possible.

[0071] The present invention uses pure water with lower conductivity to perform a fourth pure water wash after the second and third pure water washes, in order to prevent the conductivity of water on the surface of the substrate from affecting the electrophoresis effect.

[0072] The present invention sequentially performs a first electrophoretic ultrafiltration cleaning and a second electrophoretic ultrafiltration cleaning after cathode electrophoresis. The cleaning liquid used is small molecule substances, such as impurity ions, small molecule solvents, etc., which are circulated and precipitated from the electrophoretic paint through the ultrafiltration unit. The purpose of ultrafiltration cleaning is to remove floating paint attached to the surface of the electrophoretic coating, improve the appearance of the coating and recover the electrophoretic coating.

[0073] The present invention sequentially performs the fifth pure water washing and the sixth pure water washing after the second electrophoretic ultrafiltration washing, the purpose of which is to remove the floating paint and ultrafiltrate on the surface of the electrophoretic coating film to avoid affecting the subsequent coating.

[0074] Components

[0075] The parts provided by the present invention are treated by the electrophoretic coating process. After being treated by the electrophoretic coating process, the parts of the present invention are still free of rust after a 1000-hour salt spray test, have stronger corrosion resistance than existing parts, and can work longer in a humid environment.

[0076] In some embodiments of the present invention, the parts are steel-aluminum hybrid frames or steel-aluminum hybrid bodies. The paint layers of the body and frame are easily damaged by road mud and gravel splashing, and road water and road salt keep the body and frame in a humid environment for a long time, which accelerates corrosion. The steel-aluminum hybrid frame or steel-aluminum hybrid body of the present invention has better anti-corrosion performance after being treated by the above-mentioned electrophoretic coating process, and the body and frame can be rust-free for a long time after the topcoat is damaged.

[0077] vehicle

[0078] The parts used in the vehicle provided by the present invention are treated by the above-mentioned electrophoretic coating process and are still free of rust after a 1000-hour salt spray test. Therefore, the vehicle using the parts can work for a longer time in a humid environment, and the body and frame can be free of rust for a longer time after the topcoat is damaged.

[0079] Example

[0080] The technical scheme of the present invention is described in detail by way of examples below. If the manufacturer's brand or preparation method is not specified, the raw materials, equipment or solvents used are all common raw materials, equipment or solvents on the market. Unless otherwise specified, the raw materials of the same name used in the following examples and comparative examples are all the same raw materials.

[0081] The cold-rolled steel sheets used in the following embodiments and comparative examples are all made of the same material, and the cathode electrophoretic liquid used is prepared by HT-8000C of Kansai Paint, and the HT-8000C cathode electrophoretic paint includes color paste F-1, emulsion F-2, neutralizer F-3A, and replenishing solvent F-3E. Taking the target preparation of 3500g cathode electrophoretic liquid as an example, the raw materials are taken according to the following volume ratio: color paste (F-1): emulsion (F-2): pure water: neutralizer (F-3A) = 321: 1717: 1457.4: 4.6, and replenishing solvent (F-3E) is added according to 1.0wt% of the cathode electrophoretic liquid content, and mixed evenly to obtain the cathode electrophoretic liquid. The degreasing agent is a common commercially available degreasing agent.

[0082] Example 1

[0083] This embodiment provides an electrophoretic coating process, comprising the following steps:

[0084] (1) A zirconization solution is prepared using hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite: the Zr element concentration in the zirconization treatment solution is 2.3 pt, the pH value is 4.4, the free fluoride ion (FF) concentration is 40 mg / L, the aluminum nitrate concentration is 50 ppm, and the sodium nitrite concentration is 50 ppm.

[0085] (2) electrophoretic coating, the process flow of electrophoretic coating is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing;

[0086] (2.1) Zirconization pretreatment: Immerse the cold-rolled steel sheet in the zirconization solution at 30°C for 120 seconds, remove it, and proceed to the next step;

[0087] (2.2) Cathodic electrophoresis: Immerse the cold-rolled steel sheet in the electrophoresis solution at 30°C, apply voltage for 200 seconds, remove it, and proceed to the next step.

[0088] Comparative Example 1

[0089] This comparative example provides an electrophoretic coating process, comprising the following steps:

[0090] (1) A zirconization solution is prepared using hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite: the Zr element concentration in the zirconization treatment solution is 9 pt, the pH value is 4.4, the free fluoride ion (FF) concentration is 70 mg / L, the aluminum nitrate concentration is 50 ppm, and the sodium nitrite concentration is 50 ppm.

[0091] (2) electrophoretic coating, the process flow of electrophoretic coating is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing;

[0092] (2.1) Zirconization pretreatment: Immerse the cold-rolled steel sheet in the zirconization solution at 30°C for 120 seconds, remove it, and proceed to the next step;

[0093] (2.2) Cathodic electrophoresis: Immerse the cold-rolled steel sheet in the electrophoresis solution at 30°C, apply voltage for 200 seconds, remove it, and proceed to the next step.

[0094] Comparative Example 2

[0095] This comparative example provides an electrophoretic coating process, comprising the following steps:

[0096] (1) A zirconization solution is prepared using hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride, and sodium nitrite: the Zr element concentration in the zirconization treatment solution is 1 pt, the pH value is 4.4, the free fluoride ion (FF) concentration is 40 mg / L, the aluminum nitrate concentration is 50 ppm, and the sodium nitrite concentration is 50 ppm.

[0097] (2) electrophoretic coating, the process flow of electrophoretic coating is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing;

[0098] (2.1) Zirconization pretreatment: Immerse the cold-rolled steel sheet in the zirconization solution at 30°C for 120 seconds, remove it, and proceed to the next step;

[0099] (2.2) Cathodic electrophoresis: Immerse the cold-rolled steel sheet in the electrophoresis solution at 30°C, apply voltage for 200 seconds, remove it, and proceed to the next step.

[0100] Table 1

[0101]

[0102]

[0103]

[0104] Table 2

[0105]

[0106] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A zirconization treatment solution, characterized in that: The zirconization treatment solution comprises hexafluorozirconic acid, aluminum nitrate, nitric acid, hydrogen fluoride and sodium nitrite.

2. The zirconization treatment solution according to claim 1, characterized in that: The Zr element concentration in the zirconization treatment solution is 2-5 pt, the pH value is 3.8-4.5, the free fluoride ion concentration is 20-50 mg / L, the aluminum nitrate concentration is 50-100 ppm, and the sodium nitrite concentration is 50-100 ppm.

3. An electrophoretic coating process, characterized in that: The process flow of the electrophoretic coating process is: flood washing → pre-degreasing → main degreasing → first water washing → first pure water washing → zirconization pretreatment → second pure water washing → third pure water washing → fourth pure water washing → cathode electrophoresis → first electrophoretic ultrafiltration washing → second electrophoretic ultrafiltration washing → fifth pure water washing → sixth pure water washing; The zirconization pre-treatment comprises: The parts are immersed in the zirconization treatment solution of claim 1 or 2 for 120s to 140s at 20 to 40°C, and then taken out and the next step is carried out.

4. The electrophoretic coating process according to claim 3, characterized in that: The cathode electrophoresis comprises: immersing the parts in a cathode electrophoresis solution at 28 to 32° C. for 180 to 220 seconds.

5. The electrophoretic coating process according to claim 3, characterized in that: The parts include steel parts and aluminum parts.

6. The electrophoretic coating process according to claim 3, characterized in that: In the cathode electrophoresis solution: The solid content is 19 wt% to 25 wt%; and / or, The ash content is 15wt% to 21wt%; and / or, pH value is 5.6 to 6.7; and / or, The electrical conductivity is 1200 to 2000 μs / cm; and / or, One voltage is 190~210V; and / or, The second stage voltage is 285~315V.

7. The electrophoretic coating process according to claim 3, characterized in that: The conductivity of the water in the second and third pure water washings is controlled to be ≤500 μs / cm; and / or, The free alkali content of the degreasing agent used in the pre-degreasing and main degreasing is 9.0-12.0, and the treatment temperature is 42-50°C.

8. A component, characterized in that: The parts are treated by the electrophoretic coating process described in any one of claims 3 to 7.

9. The component according to claim 8, characterized in that: The component is a steel-aluminum composite frame or a steel-aluminum composite body.

10. A vehicle, characterized in that: Comprising the parts described in claim 8 or 9.

Citation Information

Patent Citations

  • Surface zirconization treatment process before car body coating

    CN108998781A

Cited By

  • Preparation method of 40Cr steel corrosion-resistant zirconium film

    CN121023491A